The effectiveness of the parenting training program with a futuristic rational approach on the creativity of female children - Somyeh Moddaresi; Gholam Ali Afrooz; Zahra Naghsh; Masoud Lavasani (مطالعات روانشناسی تربیتی)
The concept of rationality and wisdom has a long history in religious and philosophical texts. On the other hand, nowadays, the importance of parenting and the use of approaches appropriate to the Iranian culture of parenting styles and its impact on the upbringing and future of children is not hidden from anyone. This research was carried out with the aim of the effectiveness of the parenting education program with a futuristic rational approach on the creativity of primary school children. The working method of this research is semi-experimental with a pre-test-post-test design with a control group. The research community included parents of elementary school students in Tehran in the academic year of 1401-1400, according to the entry criteria, 30 people were randomly divided into two experimental groups (they were taught rational and futuristic rational during 10 sessions) and the control group (without receiving intervention) were replaced. Torrance's creativity test (1989) was used in this research. The results of the post-test stage data were also analyzed with the MANCOVA test. The results of multivariate covariance analysis show that there is a significant difference between children's creativity in the subscales (elaboration, fluidity, initiative and flexibility) with the control group (P<0.001). Based on the obtained findings, it can be concluded that futuristic rational parenting training is effective on the creativity of primary school children. And this training can be used as an approach appropriate to Iranian culture.